2018
DOI: 10.1186/s12891-018-2168-6
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic debridement of anterior ankle impingement in patients with chronic lateral ankle instability

Abstract: BackgroundThe aim of this study was to determine the functional and radiological outcomes of arthroscopic treatment of anterior ankle impingement (AAI) in patients with chronic lateral ankle instability (CAI).MethodsAll patients with CAI between June 2012 and May 2015 were invited to participate in this investigation. All of them accepted open modified Broström repair of lateral ankle ligaments and were divided into two groups: AAI group (with anterior ankle impingement) and pure CAI group (without anterior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…The ankle joint is the most commonly injured part of the human motion system. The most vulnerable part is the lateral collateral ligament of the ankle joint (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The ankle joint is the most commonly injured part of the human motion system. The most vulnerable part is the lateral collateral ligament of the ankle joint (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with ankle instablity, taking advantage of the anterior median view portal and using the three‐portal approach, it was easy to position the distal fibula through the lateral working portal. The factors related to the poor treatment of ankle impact arthroscopy include patients being older, longer delay from trauma to surgical treatment, ankle joint relaxation, and osteoarthritis joint space narrowing 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 7 studies that evaluated sex as a variable, 4 (57%) reported a difference in findings. 5,9,29,50 In the study by Baums et al, 5 68% of male patients and 80% of female patients had AMI/ALI with a traumatic ankle sprain. Buda et al 9 conducted a multivariate analysis and showed that male patients had a significantly worse outcome at a 6-year follow-up (P = .03).…”
Section: Sex-related Outcomesmentioning
confidence: 97%
“…Of the 28 studies, 7 (25%) included sex-specific analysis when evaluating outcomes. 5,9,11,29,46,47,50 However, 4 (14%) failed to report sex even as a demographic variable. 3,25,32,34 Of the 24 studies that included demographic information, there were 1053 (61%) male patients and 685 (39%) female patients.…”
Section: Sex-related Outcomesmentioning
confidence: 99%